Sоme Оpiniоns Аbоut Teаcher’s Rоle in Fоreign Lаnguаge Clаsses - Shоkhistаkhоn Nurаlievа (European Journal of Life Safety and Stability (2660-9630), 2022)
In the article were analyzed the role of teachers in foreign language classes for motivating and guiding language learners.